Managerial Accountability in Health Right Fulfillments of the Physical Disabilities - Untari, Zabella Intan Widhi; Nurhaeni, Ismi Dwi Astuti (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Managerial accountability in the fulfillment of health rights of physically disabled people is of importance to realize equality in public services. This article aims to analyze forms of managerial accountability and its patterns of relationships in the public service delivery. This research is conducted in the Physical Disability Rehabilitation Service Center or Balai Besar Rehabilitasi Sosial Bina Daksa (BBRSBD) Prof. Dr. Soeharso with qualitative method. Data is collected through in-depth interviews, observation, and documentation. It reveals that managerial accountability is built on organization in terms of finance, human resources, and assets while it is predominantly manifested vertically in nature. Improvements towards balancing this pattern of managerial accountability with horizontally manifested one in public service delivery is crucial in order to better fulfillment of health rights of the physical disabled people.